Pengaruh Kualitas Produk dan Promosi terhadap Keputusan Pembelian Studi Empiris pada Pengguna Tokopedia - Ronaldi, Irvan; Fajri, Ahmad; Moulida, Dhelia Rahma; Anreani, Neni; Daryati, Daryati; Yulianto, Yulianto (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The purpose of this study is to examine and demonstrate how product quality and promotions affect purchasing decisions on Tokopedia. The population of this study consists of students from the Management Study Program at the Faculty of Economics and Business, Universitas Pamulang. A total of 60 respondents were used as samples in this study. The research methodology employed is purposive sampling combined with nonprobability sampling. The results of the study show a relationship between the dependent variable, purchasing decisions, and the independent variables, product quality and promotions. The T-test, based on partial testing, indicates that product quality significantly and positively influences purchasing decisions. Additionally, the promotion variable also shows that promotions significantly and positively influence consumer purchasing decisions. It can be concluded that factors related to product quality and promotions have a significant and positive effect on purchasing decisions. Product quality and promotions explain 43.8% of the Coefficient of Determination (Adjusted R Square) value of 0.438, which explains purchasing decisions, while other factors not included in this study account for the remaining 56.2%.